1982
DOI: 10.1007/bf00433730
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine from cigarette smoking increases circulating levels of cortisol, growth hormone, and prolactin in male chronic smokers

Abstract: Results of this study indicate that nicotine from cigarette smoking increases circulating levels of cortisol, growth hormone, and prolactin in male chronic smokers. Previous studies have not addressed the question of whether the stimulus for smoking-related hormone release is the 'stress' of smoking or a pharmacologic action of nicotine and other tobacco substrates. Nicotine exposure is controlled in this study by allowing each subject to smoke only two 2.0 mg nicotine cigarettes during one experimental sessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
108
2
5

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(126 citation statements)
references
References 23 publications
11
108
2
5
Order By: Relevance
“…The finding of increased cortisol levels in smoking subjects is in accordance with other studies (e.g. Wilkins et al, 1982; Steptoe and Ussher, in this issue).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The finding of increased cortisol levels in smoking subjects is in accordance with other studies (e.g. Wilkins et al, 1982; Steptoe and Ussher, in this issue).…”
Section: Discussionsupporting
confidence: 93%
“…PTSD (Neylan et al 2005). Also acute effects of smoking on the HPA-axis have been found (Wilkins et al, 1982;Kirschbaum et al, 1992 Summarizing, although there seem to be associations between traumatic stress and smoking, traumatic stress and cortisol, and between smoking and cortisol, the relationships between traumatic stress, smoking, and cortisol have not yet received much attention. This is the first study to explore the relationships between PTSD, posttraumatic depression, smoking and levels of cortisol in a sample of trauma survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies also showed that high-nicotine cigarettes increase serum GH levels. 20,21 Gapstur et al found that greater alcohol intake and, to a lesser extent, greater number of cigarettes smoked per day, were associated with lower serum IGF-I concentrations in both Black and White men. Smoking was also inversely associated with IGFBP-3, but only in White men.…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates multiple possibilities related to emotion-related differences in the dynamics of nicotine addiction. Systemic increases in cortisol secretion can result from exposure to high daily stress as well as from smoking (Wilkins et al 1982;Seyler Jr. et al 1984). High anger experience is usually associated with enhanced physiological activity and greater impact of environmental stressors (Suarez et al 1998;Bongard and al'Absi 2005).…”
Section: Discussionmentioning
confidence: 99%